CROSSOVER-BEHAVIOR OF THE UNIAXIAL DIPOLAR FERROMAGNET - Chalker, J; Gehring, G (1979)
Crossover behaviour in three-dimensional, uniaxial dipolar ferromagnets is investigated using the spherical model approximation to calculate the effective susceptibility exponent. This enables one to consider both the Ising-mean-field and Ising-dipolar crossovers together. It is found that the temperature at which the latter occurs depends strongly on the spin-wave stiffness as well as the relative dipolar strength.